Immunological aspects of corneal graft rejection and own experience in immunosuppressive therapy in high risk patients - Kamińska, Anna; Szaflik, Jerzy; Minkiewicz-Timler, Grażyna; Sybilska, Małgorzata; Pawluczyk-Dyjecińska, Martyna; Smolarek, Monika (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
The aim of the study was to present factors responsible for immune privilege of corneal graft, pathogenesis of immunological corneal graft rejection, and the influence of immunosuppressive therapy on keeping clarity of corneal graft. We also present retrospective evaluation of prophylactic immunosuppressive therapy in high-risk patients and in cases of graft rejection, in group of patients after corneal transplantation performed in Department of Ophthalmology in years 2001-2003. 349 cases of penetrating keratoplasty, lamellar or penetrating with limbal transplantation were analyzed. Condition requiring keratoplasty, surgical procedures, profile of immunosuppressive therapy, number of recurrences of corneal graft rejection and changes of visual acuity were evaluated. Immunosuppressive therapy with oral corticosteroids and systemic Cyclosporine allow to keep clarity of corneal graft and useful visual acuity in 60% cases of high-risk patients.